2017
DOI: 10.1364/ao.56.006427
|View full text |Cite
|
Sign up to set email alerts
|

Black phosphorus flakes covered microfiber for Q-switched ytterbium-doped fiber laser

Abstract: We demonstrate a passively Q-switched ytterbium-doped fiber laser based on black phosphorus (BP) flakes covered microfiber. The BP saturable absorber is fabricated by sandwiching a microfiber between two pieces of polydimethylsiloxane supported BP flakes film, which is prepared by the mechanical exfoliation method. In this case the BP flakes can be well protected from the action of air and moisture. By incorporating BP flakes covered microfiber into a ytterbium-doped ring fiber laser, stable and reliable Q-swi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…These early efforts have promoted the rapid development of layered materials in Q‐switched lasers. For example, Q‐switched fiber lasers based on layered materials including graphene, topological insulators, TMDCs, and BP, have been obtained, as illustrated in Table . It can be seen that these lasers have excellent performance in output power, pulse width, repetition frequency, and peak power, which is not inferior to the traditional lasers based on semiconductor saturable absorption mirrors and carbon nanotubes.…”
Section: Versatile Pulsed Lasers Using 2d Layered Materialsmentioning
confidence: 99%
“…These early efforts have promoted the rapid development of layered materials in Q‐switched lasers. For example, Q‐switched fiber lasers based on layered materials including graphene, topological insulators, TMDCs, and BP, have been obtained, as illustrated in Table . It can be seen that these lasers have excellent performance in output power, pulse width, repetition frequency, and peak power, which is not inferior to the traditional lasers based on semiconductor saturable absorption mirrors and carbon nanotubes.…”
Section: Versatile Pulsed Lasers Using 2d Layered Materialsmentioning
confidence: 99%
“…In 2017, Huang et al achieved a Q-switched laser at 1064 nm where microfibers were sandwiched by BP flakes to integrate SA, providing an effective way to prolong the life of BP flakes by isolating them from the air [ 297 ]. In 2019, Wang et al demonstrated both Q-switched and mode-locked lasers based on BP by inserting polarization-maintaining fiber Bragg gratings [ 298 ].…”
Section: Applications Of 2d Materials In Ultrafast Lasersmentioning
confidence: 99%
“…Since the rst BP-based SA (BP-SA) deposited around a microber was proposed, 15 there has been much progress in the eld of BP-based pulse laser generation. [16][17][18][19][20][21] BP-SA can be manufactured via liquid phase exfoliation technology 14 or the mechanical exfoliation method. 22 Zhang et al reported few-layer selenium-doped black phosphorus with high quality and low cost in 2017.…”
Section: Introductionmentioning
confidence: 99%